4 - The reform of public universities in Tanzania: Governmentality and the exercise of power - Catherine Chinenye Maduekwe; Beverly Thaver (African Sociological Review, 2019)
In general, African nations, from the mid-20th century onwards, have witnessed an increasing and massive expansion in the university1 sector. By the first decade of the 21st century, as the sector expanded even further, so did the pressure for policy reforms increase from across the globe and the African regions. These reforms were established as instruments for advancing national development, namely, within the trajectory of reducing poverty through sustainable (economic and social) growth. Drawing on the East African nation of Tanzania, this article focuses on the implementation of a policy reform in three public universities. The reform (framed within the policy narrative of strategies for growth and the reduction of poverty), is referenced in Swahili as “Mkakati wa Kukuza Uchumi na Kupunguza Umaskini”. The dynamics associated with the implementation process are interpreted within the framework of Michel Foucault’s theory of Governmentality which is premised on a particular form and exercise of power relations. In this respect, the article seeks to understand how the reform was drawn upon as a regime of governance, namely, as regulating behaviour in three universities in Tanzania, with specific reference to the mandates of ‘access’ and ‘quality’.